REBO WEKASAN MENURUT PERSPEKTIF KH. ABDUL HAMID DALAM KANZ AL-NAJĀḤ WA AL-SURŪR - Umma Farida (Jurnal Theologia, 2019)
This article aims to describe Rebo Wekasan and its various rituals by focusing on the thoughts of KH. Abdul Hamid Kudus have written particularly in his work Kanz al-Najāḥ wa al-Surūr. The data was collected through the documentation method and analyzed critically. This study found that Rebo Wekasan ritual is local wisdom combined with Islamic values. The origins of rituals carried out by some Indonesian Muslim people, especially on Java, often refer to the opinion of KH. Abdul Hamid Kudus. His thought is that Allah reveals various kinds of disasters and trials on the last Wednesday of the month of Ṣafar, so that people were advised to perform certain rituals such as sunnah prayers, reading verses of the Qur'an, ṣalawat, and praying. These rituals are indeed practiced in several areas in Java with various modifications of local traditions which are manifested in the form of cultural carnivals, Quranic recitations, and selamatan (local gathering). However, his book is an inseparable from criticism, especially criticisms of sources that are considered less authoritative and critical in terms of the quality of the hadith about Rebo Wekasan.